Explaining Anglo-Saxon military efficiency: the landscape of mobilization. (18th November 2016) - Baker, John; Brookes, Stuart
Abstract: The importance of warfare in Anglo-Saxon England is widely accepted, but the processes by which armies were put in the field are only partially understood, with most discussion focusing on the economic logistics rather than the spatial practicalities of mobilization. Yet such a system underpinned recorded military actions and must have evolved in response to changing military organization in the late Anglo-Saxon period. Through an assessment of documentary references to sites of muster, and by using a multidisciplinary landscape-focused approach, this article examines possible traces of that system – especially those preserved in place-names – and relates them to later Anglo-Saxon administrative geography.